Fever and Rash Syndrome: A review of clinical practice guidelines in the differential diagnosis - Mohammed Jafar Saffar; Hiva Saffar; Soheila Shahmohammadi (Mazandaran University of Medical Sciences, 2013)
Fever accompanied by rash is a common finding in pediatric patients. Although, in most cases, the disease is trivial, in some cases it may be the first and/or the sole manifestation of a serious and life threatening condition in patients. The spectrum of differential diagnosis is broad and many different infectious and some noninfectious agents cause this syndrome. To establish a timely diagnosis, providing appropriate therapy and considering proper preventive measures if necessary, a systematic approach relying on a clear history, careful clinical examination along with particular attention to epidemiological features are the most important factors to pursue this syndrome. In this paper, the aim is to give an overview of how to deal with these patients clinically to establish a timely probable diagnosis of patients, providing proper early medical intervention without applying specific laboratory tests.